Dialogue on Commercialization of Climate- Smart Agricultural Technologies, Innovations and Management Practices in Eastern & Central Africa - Ilakut, Ben; Barungi, Julian; Okonya, Joshua Sikhu; Odeke, Moses; Recha, John W.M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The Association for Strengthening Agricultural Research in Eastern and Central Africa (ASARECA) recognizes the critical role that the private sector, research organizations, farmer organizations, policy makers, extension workers and media play in scaling up and commercialization of climaterelevant TIMPs. However, the adoption and use of several new agricultural technologies by smallholder farmers remains relatively low in the region resulting in low production (crop yields) on farms, poor quality and high postharvest losses. Reducing the yield gap of improved crop varieties for instance requires concerted efforts of both the technology innovators and those involved in its dissemination and regulation. Based on the foregoing, ASARECA organized a dialogue on the commercialization of climate-relevant agricultural Technologies, Innovations, and Management Practices (TIMPs) in Eastern and Central Africa for the private sector, climate scientists, research organizations, policy makers, extension workers, and media to discuss commercialization of climate-relevant TIMPs.